Unia Europejska - wielojęzyczny problem? - Konieczna, Nell (Stowarzyszenie Mage.pl, 2013)
Polityka wielojęzyczności Unii Europejskiej kształtowana była etapami, dzięki czemu została głęboko zakorzeniona w świadomości europejskiej. Wraz z rozwojem pojawiły się także problemy związane z wykładnią, jednolitością stosowania prawa oraz komunikacją. Problem pluralizmu skłania do refleksji nad możliwościami zmiany istniejącego systemu , jednakże trudność sprawia znalezienie rozwiązania tak jasnego i uniwersalnego aby zminimalizować konsekwencje pluralizmu językowego.The politics of polyglotism in European Union was shaped in stages, thanks to that it has rooted deeply into european consciousness. With such development several problems has appeared, with the interpretation of law, the uniform applications of law and comunnication. The problem of linguistic pluralism brings the reflexions on the possibilities of changes in the existing system, however it is difficult to find such clear and universal solution for reduction the consequences of linguistic pluralism.

The politics of polyglotism in European Union was shaped in stages, thanks to that it has rooted deeply into european consciousness. With such development several problems has appeared, with the interpretation of law, the uniform applications of law and comunnication. The problem of linguistic pluralism brings the reflexions on the possibilities of changes in the existing system, however it is difficult to find such clear and universal solution for reduction the consequences of linguistic pluralism.
Keywords: tłumaczenia w UE; zasada autentyczności; zasada tożsamości narodowej; przekład tekstów prawnych; polityka wielojęzyczności; języki autentyczne